Paleobiogeography of the late Pleistocene pampatheres of South America - Scillato, Gustavo Juan (2005)
This paper deals mainly with the paleobiogeography of the South American Pampatheriidae of the late Pleistocene. Through analysis, we conclude that (1) the species of Quaternary pampatheres may be distinguished clearly by their carapace scutes and craniodental characters; (2) there are two pampathere genera in the South American Quaternary, Pampatherium and Holmesina; (3) no more than one species of each genus occurs in association at a single locality or site; (4) Holmesina differentiated in North America, entered South America during the Late Pleistocene, and later experienced speciation probably related to Late Pleistocene and Holocene climate changes; (5) Pampatherium differentiated in South America, and its speciation process produced a second immigration of pampatheres to North America; and (6) the use of contrasting environments may be observed among the Quaternary pampatheres.